NEW RECORD OF Synhimantus (Dispharynx) nasuta (RUDOLPHI, 1819) CHABAUD, 1975 (NEMATODA, ACUARIOIDEA) IN THE YELLOW VENTED BULBUL (Pycnonotus goivier) FROM EAST KALIMANTAN, INDONESIA - Dewi , Kartika; Irham, Mohammad; Prawiradilaga , Dewi M.; Kawakami, Kazuto (Treubia, 2015)
Abstract not available